Multiple Comorbid Conditions among Middle-Aged and Elderly Hemophilia Patients: Prevalence Estimates and Implications for Future Care - Aroub A. Khleif; Nidra Rodriguez; Deborah Brown; Miguel A. Escobar (Journal of Aging Research)
Introduction. Advances in hemophilia care and treatment have led to increases in the life expectancy among hemophiliacs. As a result, persons with hemophilia are reaching an older age and experiencing various age-related health conditions never seen before in this population. Aim. To determine the prevalence of comorbidities among middle-aged and elderly hemophilia A and hemophilia B patients. Methods. Retrospective chart review among all hemophilia patients, who attended the Gulf States Hemophilia and Thrombophilia Center. Results. All patients had at least one comorbid condition other than hemophilia, and the majority had between 3 and 6 comorbidities. The most common conditions identified were chronic hepatitis C, hypertension, HIV, chronic arthropathy, and overweight/obesity. Conclusions. Since persons with comorbidities are more likely to have poorer health outcomes and require greater care in managing their health needs, caring for aging hemophiliacs is likely to pose various social and economic challenges for both patients and providers.